Isolation and characterisation of metal-tolerant actinomycetes from a Karstic Cave in Malaysia / Yap Siew Mei - Yap, Siew Mei (2015)

(untitled)
The main objective of this study was to isolate actinomycetes from environmental samples collected from the Dark Caves, a karstic cave located in Batu Caves, Kuala Lumpur, Malaysia. The environmental samples were collected from different parts of the cave including cave ceilings, columns, soils and stalagmites. Results showed the number of actinomycetes isolated from cave soils was the highest among all sampling sites, followed by cave wall, cave columns and the lowest was from stalagmite. A few types of isolation media were used to selectively isolate actinomycetes and the results showed higher percentage of total actinomycete isolates were obtained from isolation media SM3 (a glucose peptone medium), humic-acid yeast-extract agar and tap water agar. A total of 113 actinomycete strains was isolated and characterized in terms of their morphological characteristics, ability to produce diffusible pigments and 16S rRNA gene restriction fragment patterns. Morphological observations showed many of the actinomycete strains belonged to the yellow colour series and was presumptively classified as Streptomyces spp. Analysis of 16S rRNA gene restriction fragment patterns revealed that the majority of actinomycete strains belonged to the genus Streptomyces but there were several strains belonging to the genera Nocardia, Lentzea and Rhodococcus. Additionally, the actinomycete strains were tested for tolerance towards copper and nickel at concentrations ranging from 50-200μg/mL. Results showed 18.6% and 51.3% of the isolated actinomycetes were able to grow on MSM supplemented with copper and nickel respectively ranging from concentration of 50μg/ml - 200μg/ml. This study reveals that a variety of actinomycetes could be found in karstic caves of Malaysia and may represent new sources of unreported genera and species.